Determination of the onset of ventricular tachycardia - Mohd Afzan, Othman; Norlaili, Mat Safri; Sinan S., Mohammed Sheet (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/